ARTISTIC AND COMPOSITIONAL ELEMENTS OF A NORTH AMERICA PEOPLE`S COSTUME AS A CREATIVE SOURCE FOR THE DEVELOPMENT OF A CLOTHES COLLECTION - Приходько-Кононенко, І. О.; Винничук, М. С.; Васильєва, О. С.; Пристав, Т. В.; Маслікова, М. І. (Art and Design, 2020)
To determine the artistic and compositional features of ethnic costume of the peoples of North America for design-projection of the modern collections of women`s clothes. The visual-analytical and the literary-analytical methods, as well as the method of synectics, etc. are used. Based on the analysis of artistic and compositional solutions for ethnic costumes of the peoples of North America, in particular, Crow, Creek, Navaho, Pancho and Pueblo, their inherent elements and decorations are identified, and the possibility of their use as a creative source for the designing of modern collections of clothes in ethnic style, using the latest fashion trends and the draping method, is presented. Compositional and constructive, and decorative solutions for the models of women`s clothes are systematized in accordance with the fashion trends of the SS 19/20 season; specific artistic and compositional elements of the ethnic costume of the Indians of North America are distinguished; possible types of finishing are described, and their application in design-projecting of the collections of clothes are presented. Artistic-design and constructive-technological solutions for the models of women`s clothes using the artistic and compositional elements of the national costume of the Indians of North America are developed.